Embedded MoS2-PANI nanocomposites with advanced microwave absorption performance. (29th September 2020) - Ma, Jialin; Ren, Hengdong; Liu, Zhenying; Zhou, Jun; Wang, Yueqin; Hu, Biao; Liu, Yin; Kong, Ling Bing; Zhang, Tianshu
Abstract: A microwave absorber of MoS2 -PANI with three-dimensional spherical structure was synthesized. The absorber was prepared by one-step hydrothermal strategy of a two-dimensional nanoflower-like MoS2 and in-situ oxidation polymerization reaction with an aniline monomer under ice bath conditions. It can be clearly seen from the SEM characterization that the structure of this three-dimensional MoS2 -PANI microwave absorber is composed of a soft flower-like MoS2 as a carrier and a successful intercalation of two-dimensional nano-rod PANI. The effects of aniline monomer, initiator and molybdenum disulfide on the microwave absorption properties of MoS2 -PANI nanocomposites were investigated by adjusting different mass ratios. The results show that the optimized reflection loss (RL) of the MoS2 -PANI nanocomposites after interlayer is −59.78 dB, a matching thickness of 3.44 mm and an effective absorption frequency range of 6.56–9.68 GHz (RL < -10 dB), covering C-Band and X-band. The outstanding microwave absorption performance of the MoS2 -PANI nanocomposites is attributed to three factors, including enlarged specific surface area, reduced particle size and increased electrical conductivity. Graphical abstract: Image 1